Teaching World Languages for Specific Purposes : A Practical Guide - Ruggiero, Diana M. (Book collections on Project MUSE., 2022)
"This proposed book seeks to provide teachers with a very practical way to approach the creation of languages for specific purposes teaching curriculum for any world language. Languges for specific purposes refers to the teaching of a language in a content-based professional area, such as business and medicine. As these courses grow in interest, there remains a need for a critical overview and practical guide to the teaching of world languages for specific purposes (WLSP) in the broadest sense. This book seeks to fill this void in the literature. Diana Ruggiero, active in the WLSP community, aims to write a very approachable and concise book that takes teachers through the process of developing a curriculum, course, or program for WLSP in their language. The book will begin with an overview of the scholarship and purpose of WLSP in general to provide a grounding for teachers. There is no book currently available that provides teachers with this hands-on information"--